2017
DOI: 10.3390/w9070552
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Climatic Factors and Human Activities with Water Level Fluctuations in Qinghai Lake in the Northeastern Tibetan Plateau, China

Abstract: Abstract:Changes in the water level of Qinghai Lake, the largest inland lake in China, directly affect the ecological security of Qinghai province and even the northwest of China. This study aimed to investigate the lake level and identify causes of changes in the lake level of Qinghai Lake. The results showed that the lake level was 3196.55 m in 1959 and gradually declined to 3192.86 m in 2004, with an average decreasing rate of 8.2 cm·year −1 over 45 years. However, the lake level increased continuously by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The lake water budget is mainly contributed by precipitation and runoff from the five largest rivers: the Buha River, the Shaliu River, the Haergai River, the Ganzi River, and the Daotang River. The largest 286‐km‐long Buha river contributes up to 46.9% of surface runoff to the lake, while the second‐largest Shaliu River contributes around 14.5% (Chang et al, 2017). About 90% of the annual rainfall in the lake basin takes place between May and September (G. Q. Zhang et al, 2011).…”
Section: Study Area and Datamentioning
confidence: 99%
“…The lake water budget is mainly contributed by precipitation and runoff from the five largest rivers: the Buha River, the Shaliu River, the Haergai River, the Ganzi River, and the Daotang River. The largest 286‐km‐long Buha river contributes up to 46.9% of surface runoff to the lake, while the second‐largest Shaliu River contributes around 14.5% (Chang et al, 2017). About 90% of the annual rainfall in the lake basin takes place between May and September (G. Q. Zhang et al, 2011).…”
Section: Study Area and Datamentioning
confidence: 99%
“…For example, Han et al [23] found that the variation of precipitation and the operation of the Three Gorge Reservoir mainly affected the variation of water level in the Dongting Lake region. However, Chang et al [24] revealed that the water level of Qinghai lake depended more on climatic factors than on anthropogenic factors. Using the Cryosat-2 SARIn model data from 2010 to 2015, Jiang et al [21] revealed that the driving factors for water level change in the Qinghai-Tibet Plateau were variable and the autumn/winter temperature played an important role in the lake water level change.…”
Section: Introductionmentioning
confidence: 99%
“…Models play a significant role in assessment of water yield, because they can estimate and simulate the spatial distribution of water yield [10]. However, more and more attention has been paid to the prevent the west from desert spreading from the east, and is an important node to maintain ecological security in the northeast of Qinghai-Tibet Plateau [34,35]. In general, the temperature increases from northwest to southeast in the watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Qinghai lake is the largest inland saline lake in China. Qinghai lake watershed is a natural barrier to Water 2020, 12, 11 3 of 18 prevent the west from desert spreading from the east, and is an important node to maintain ecological security in the northeast of Qinghai-Tibet Plateau [34,35]. In general, the temperature increases from northwest to southeast in the watershed.…”
mentioning
confidence: 99%